Reflexive Narratives as a Tool to Confront University Researcher Roles in Engaged Scholarship - Mellinee Lesley; Whitney Beach; Elizabeth Stewart; Johanna Keene (The University of Alabama, 2023)
The purpose of this qualitative study was to develop a deeper understanding of what it means to be an engaged scholar by examining reflexive narratives written by university researchers about their experiences conducting participative research. Writing reflexive narratives provided tools that permitted the researchers to parse the types of emotions and assumptions that may lead to unspoken and even unconscious bias in research. Implications for utilizing reflexive narratives in engaged scholarship research are discussed.